Pemanfaatan Sistem Informasi Manajemen Untuk Meningkatkan Efisiensi Operasional Perusahaan - Nurhawa; Tri Yani, Nabila; Asadurrahman, Hud; Bonanza, Brilian (Jurnal Ilmu Ekonomi dan Bisnis, 2026)
The development of information technology encourages companies to adopt Management Information Systems (MIS) as a strategic tool to improve operational efficiency. This study aims to examine the use of MIS in supporting company operational efficiency through book reviews and relevant scientific articles. The research method used is a literature study by analyzing various literature sources in the form of textbooks and journal articles that discuss the concept of MIS, operational efficiency, and its implementation in organizations. The results of the study indicate that the implementation of MIS can improve operational efficiency by accelerating the decision-making process, integrating data across departments, reducing operational errors, and increasing work productivity. Thus, MIS plays an important role as a management support tool in achieving a company's competitive advantage.